ALD NiO Thin Films As a Hole Transport-Electron Blocking Layer Material for Photo-Detector and Solar Cell Devices. (13th April 2015) - Nam, Wook Jun; Gray, Zachary; Stayancho, John; Plotnikov, Victor; Kwon, Dohyoung; Waggoner, Shawn; Shenai-Khatkhate, Deodatta V; Pickering, Michael; Okano, Terumi; Compaan, Alvin; Fonash, Stephen J
Abstract : ALD NiO was deposited on silicon and glass substrates by applying alternative pulses of Ni(amd) (AccuDEP TM Ni, Dow Chemical), and water. The film deposition rate at 200°C was 0.25-0.45 Å/cycle. The material properties of the NiO films were characterized using FESEM, AFM, UV-Vis-NIR spectrometer, and GIXRD. The optimized thin ALD NiO film was applied to very thin (500nm) CdTe cells in order to evaluate the potential of the ALD NiO film as a HT-EBL layer. The ALD NiO integrated CdTe cells enhanced Voc and FF, and offered 15% improvement in PCE compared with the control cells.